The Potential of Rivers as Renewable Energy Power Plants - Michael Okon Bassey; Aniekan Essienubong (AKADEMI SERTIFIKASI PROFESI INTERNASIONAL, 2024)
Globally, the demand for cheap energy source has risen as a result of population growth, urbanization, and industrialization. While the electricity consumption in emerging nations like Nigeria is rising, the supply, which is often derived from fossil fuels is diminishing, leading to an energy crisis and pollution. Thus, in order to cover both the present and future energy needs, it is necessary to investigate alternate or renewable energy sources. This study seeks to offer a broad overview of the economic design consideration, practical implementation parameters, and interconnections of the key components of small hydropower plants for River Nnwankwo, in Ikot Ekpene local government area of Akwa Ibom State, Nigeria. The focus is to offer a foundational understanding of micro-hydro systems, planning, the advantages and limitations of micro-hydro energy estimation, which is a function of head and flow rate. If this exploitable source of energy could be harnessed using environmentally friendly technology, the entire energy situation in Ikot Ekpene sub urban which has a thriving population would be improved.